BUSINESS MODEL FOR SPECIAL TRADITIONAL DRINKS OF GRESIK’S IN CURCUMA AND GINGER POTION “ESON” - Vembri Aulia Rahmi; Hadi Ismanto; Suaibatul Aslamiyah; Muhammad Rosyihuddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The culinary business in Gresik Regency requires attention from at least local stakeholders, not only because of the high consumer interest in its culinary specialties but also because the market for these products is also becoming crowded and saturated. Meanwhile, the potential of this business is actually still vast, supported by the spirit of preserving local wisdom. Another problem that also arises is the level of business competition is also quite high. This study aims to determine how the BMC concept for MSEs practices in Gresik Regency. The focus of this study is to conduct observations on businesses in the culinary sector, specifically traditional beverages, such as sinom and temulawak "Eson". The results of this study revealed that the business model in this business is feasible with several recommendations regarding business management and networking, which require adaptation and alignment with current business developments. The empathy map as a business model tool shows a positive image of consumers or those who are satisfied with the product. However, in an effort to increase sales levels, marketing improvements are needed as a key to business success. Product quality is known to be good, but innovation in new flavors is possible, such as: adding different, contemporary ingredients, so that it can be an alternative to expand the market for traditional beverage products typical of Gresik Regency.